Hubungan Lama Hemodialisa dengan Kejadian Pruritus Uremik pada Pasien GGK RSUD Dr. Hardjono Ponorogo - Endah Wulandari (Politeknik Kesehatan Kemenkes Mamuju, 2019)
Hemodialysis therapy is very important to maintain condition of fluid balance in the body and prolong the life of patients with chronic renal failure (CRF). Hemodialysis doesn’t cure kidney disease completely and patients will experience various complications after the action, one of which is uremic pruritus. Uremic pruritus is generally experienced about 6 months after onset of dialysis and usually increases with the length of the patient undergoing hemodialysis. The goald of the research to know the relationship between duration of hemodialysis with uremic pruritus occurrence in CRF patients at RSUD Dr. Hardjono Ponorogo. The design research is study of correlational by using survey plan research cross sectional survey. Population in this research is all hemodialysis patients at RSUD Dr. Hardjono Ponorogo. Sample in this research is partially hemodialysis patients in April 2018 for 2 weeks. Sampling technique in this research is non-probability sampling that is consecutive sampling, while the sample is 93 respondents. The independent variable is duration of hemodialysis, dependent variable is uremic pruritus. The statistical test used Chi-Square test. The results indicates majority of the respondents undergo hemodialysis >6 months as much as 65 respondents (69.9%) and as much as 55 respondents (59.1%) didn’t experience uremic pruritus. Based on result of the test statistic Chi-Square obtained result of p=0.262 p>0.05 then Ho accepted or there aren’t relationship between duration of hemodialysis with uremic pruritus occurrence in CRF patients at RSUD Dr. Hardjono Ponorogo. Based on the result of the research can be concluded the duration of hemodialysis doesn’t affect the occurrence of uremic pruritus.